2012
DOI: 10.1128/jb.01592-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Bacterium Streptomyces davawensis JCM 4913 and Heterologous Production of the Unique Antibiotic Roseoflavin

Abstract: Heterologous expression of a set of genes present on a subgenomic fragment of S. davawensis resulted in the production of roseoflavin by the host Streptomyces coelicolor M1152. Phylogenetic analysis revealed that S. davawensis is a close relative of Streptomyces cinnabarinus, and much to our surprise, we found that the latter bacterium is a roseoflavin producer as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
58
0
10

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 61 publications
1
58
0
10
Order By: Relevance
“…1,2 It is the only biosynthesized flavin analog with antibiotic activity and binds to the flavin mononucleotide (FMN) riboswitch, thus repressing riboflavin biosynthesis. 3,4 Roseoflavin has been used in the screening of mutants for maximum riboflavin production because bacteria overproducing riboflavin are resistant to roseoflavin toxicity.…”
mentioning
confidence: 99%
“…1,2 It is the only biosynthesized flavin analog with antibiotic activity and binds to the flavin mononucleotide (FMN) riboswitch, thus repressing riboflavin biosynthesis. 3,4 Roseoflavin has been used in the screening of mutants for maximum riboflavin production because bacteria overproducing riboflavin are resistant to roseoflavin toxicity.…”
mentioning
confidence: 99%
“…he Gram-positive bacterium S. davawensis JCM 4913 (1,2) synthesizes the antibiotic roseoflavin, a structural riboflavin (vitamin B 2 ) analog (2,3). For Bacillus subtilis, S. davawensis, and Corynebacterium glutamicum, it was shown that roseoflavin is taken up via riboflavin transporters (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…[1] Drei natürliche Vitaminanaloga wurden bisher beschrieben, das Vitamin-B 1 -Analogon Bacimethrin, [2] das Vitamin-B 6 -Analogon Ginkgotoxin [3] und das Vitamin-B 2 (Riboflavin)-Analogon Roseoflavin (RoF). [5] Die bei Mikroorganismen weit verbreiteten Riboflavintransporter vermitteln dabei die effiziente Aufnahme von RoF durch die Zielzellen, [6] da sie offenbar neben Riboflavin auch RoF als Aufnahmesubstrat akzeptieren. [5] Die bei Mikroorganismen weit verbreiteten Riboflavintransporter vermitteln dabei die effiziente Aufnahme von RoF durch die Zielzellen, [6] da sie offenbar neben Riboflavin auch RoF als Aufnahmesubstrat akzeptieren.…”
unclassified
“…[11] In früheren Arbeiten zur Biosynthese von RoF wurde vorgeschlagen, dass es aus Riboflavin über 8-Demethyl-8aminoriboflavin (AF) und 8-Demethyl-8-methylaminoriboflavin (MAF) gebildet wird. [5] Ein wichtiger Schritt hin zur Identifizierung der unbekannten AF-Biosynthesegene war das Ergebnis des folgenden Genexpressionsexperiments. [13] Dieses Enzym bildet RoF aus AF (über MAF;A bbildung 1, Umwandlung von 6 in 8).…”
unclassified
See 1 more Smart Citation